Assessment of nicotine dependence symptoms in adolescents: a comparison of five indicators. Issue 4 (1st December 2002) - O'Loughlin, J; DiFranza, J; Tarasuk, J; Meshefedjian, G; McMillan-Davey, E; Paradis, G; Tyndale, R F; Clarke, P; Hanley, J
Abstract : Objective: To examine the psychometric properties, test-retest reliability, and convergent construct validity of five indicators of nicotine dependence (ND) symptoms in adolescents. Design: Analysis of baseline data from a prospective study on the natural history of ND in 1264 adolescents aged 12–13 years. Setting: Ten Montreal high schools. Subjects: 233 grade 7 students who had smoked cigarettes one or more times in the three months preceding the baseline data collection. Main outcome measures: Five indicators of ND symptoms including two that are multi-dimensional (a proxy measure of ICD-10 criteria for tobacco dependence; the Hooked on Nicotine Checklist (HONC)) and three new indicators of "symptom clusters" that emerged from principal component analysis (ND/cravings, withdrawal symptoms, self medication). Results: All five indicators demonstrated acceptable internal and test-retest reliability. The correlation between the HONC and ND/cravings was 0.910. All other correlations between indicators ranged between 0.716–0.824. There was considerable overlap in the independent correlates identified for each indicator. Conclusions: All five indicators performed well psychometrically. Until the meaning, relative importance, and usefulness of each scale is clarified in longitudinal work, decisions regarding which scale(s) are most informative will depend more on the content of the scales, the need for a multi- or unidimensional indicator, and whether or not the scale is theory based.